Transformation of Curriculum Development Based on Nationality-Oriented - Listrianti, Feriska; Mundiri, Akmal (SCAD Independent, 2020)
The transformation and development of educational institutions in Indonesia also require pesantren to make improvements while maintaining their distinctiveness. Demands for development on the one hand and religious problems on the other are two threats and challenges for pesantren. The response to the two threats is anticipated by the pesantren with the development of a distinctive curriculum that distinguishes it from other institutions. This article discusses the process of developing curriculum insight nationality-oriented in pesantren, both in terms of patterns of development, the foundation of development, and conception of development. It is then becoming the key to the success of the pesantren in instilling nationalism in santri.